AN INVESTIGATION OF LISTENING COMPREHENSION PROBLEMS ENCOUNTERED BY THE 4TH SEMESTER OF ENGLISH STUDENTS AT SRIWIJAYA UNIVERSITY - Mela Maresta; Rita Hayati; Rita Inderawati (Sriwijaya University Learning and Education International Conference, 2018)
The objectives of this study were to find out: (1) the perception of the 4th semester of English students at Sriwijaya University on listening skill, (2) kinds of listening comprehension problems encountered by the 4th semester of English students at Sriwijaya University. The samples of this study were from English students at Sriwijaya University who were in academic year 2016 and now they are in the 4th semester. They consisted of 38 Indralaya students and 35 Palembang students. The writer used descriptive research design to collect the data. The data were collected by giving a questionnaire and an interview. The result showed that: (1) they were aware of the importance of listening comprehension. Although listening was difficult for them yet, they perceived that it was really important and really needed for daily life, (2) the problems they faced in listening comprehension were limited English vocabulary, unfamiliar words, slang expressions, inability to apply strategies, lack of linguistic knowledge, rate of speech too fast to comprehend, length of the spoken text, speed rate, unclear pronunciation, unclear sound of the tape (poor equipment), variety of accents, lack of concentration.